Amalan dan pengaruh pembacaan naskhah Tulkiyamat sebagai medium dakwah dalam tradisi masyarakat Makassar - Nur Setiawati, Mappaselleng (2019)
Tulkiyamat is a classical script written in Serang script adapted from Arabic script that uses Makassar language. Such script is usually read on the first night until the seventh night when one of the family members died. This script also contains about Islamic teachings, especially the life after death, doomsday and the enjoyment of life in heaven. This study aims to find out the messages contained in the Tulkiyamat script and to examine the influence of Tulkiyamat script as a medium of traditional preaching on the changes of behaviour of Makassar’s society, located in the village of Sanrobone, Takalar district. The researcher used a qualitative method. The sampling technique used in this study is purposive sampling. The data gathered through library and field work. The data collection is conducted through documentation, interview and observation. The result of the study shows that Tulkiyamat contains the message of preaching, especially the Islamic teaching about aqidah, shariah and moral. The influence of Tulkiyamat as a medium of preaching can be seen in the scheme of attitude change from the aspect of cognitive, affective and conative of the Sanrobone society as one of life guidance in the interaction of social life. The result of a change in attitude is evident from the confession (testimony) of the people who always feel grateful, patient, tolerant and live in simplicity in the behavior of everyday life.